Intimate partner violence among pregnant women in Kenya: forms, perpetrators and associations - Mariella Stiller; Till Bärnighausen; Michael Lowery Wilson (BMC, 2022)
Abstract Background Intimate Partner violence (IPV) among pregnant women is a significant problem of public health importance. Nevertheless, there are relatively few studies which have examined the phenomenon in sub-Saharan settings. The aim of this study was to provide an overview of the prevalence, perpetrators, and associated factors of IPV during pregnancy in Kenya. Methods We were making use of the 2014 Kenyan Demographic and Health Survey (KDHS) data and included women and girls of reproductive age (15-49 years) who have ever been pregnant ( $$n=4331$$ n = 4331 ). A weighted sample of respondents who have experienced violence during pregnancy ( $$n=397$$ n = 397 ) were selected for further bivariate and multivariable logistic regression analyses in order to examine the association between IPV and socio-demographic factors. Results The prevalence of violence among pregnant women in Kenya was 9.2%, perpetrated mostly by the current husband or partner (47.6%), followed by the former husband or partner (31.5%). Physical violence was the most common (78.6%), followed by emotional (67.8%) and sexual (34.8%). Having one or two children ( $$\hbox {aOR} =0.68$$ aOR = 0.68 ; $$\hbox {CI} = 0.53{-}0.88$$ CI = 0.53 - 0.88 ), having secondary or higher education ( $$\hbox {aOR} = 0.53$$ aOR = 0.53 ; $$\hbox {CI} = 0.40{-}0.69$$ CI = 0.40 - 0.69 ) and being 18 years and above at first cohabitation ( $$\hbox {aOR} = 0.75$$ aOR = 0.75 ; $$\hbox {CI}= 0.60{-}0.94$$ CI = 0.60 - 0.94 ) and at sexual debut ( $$\hbox {aOR} = 0.65$$ aOR = 0.65 ; $$\hbox {CI}=0.53{-}0.80$$ CI = 0.53 - 0.80 ) were significantly associated with fewer reports of violence during pregnancy. Pregnant women who were divorced, separated or widowed ( $$\hbox {aOR} = 1.91$$ aOR = 1.91 ; $$\hbox {CI} =1.47{-}2.47$$ CI = 1.47 - 2.47 ), who were employed ( $$\hbox {aOR} = 1.34$$ aOR = 1.34 ; $$\hbox {CI} =1.06{-}1.70$$ CI = 1.06 - 1.70 ), who had witnessed their fathers beat their mothers ( $$\hbox {aOR} = 1.59$$ aOR = 1.59 ; $$\hbox {CI} = 1.28{-}1.97$$ CI = 1.28 - 1.97 ) and who had primary education ( $$\hbox {aOR} = 1.53$$ aOR = 1.53 ; $$\hbox {CI} = 1.11{-}2.14$$ CI = 1.11 - 2.14 ) were significantly more likely to experience violence. Conclusions To prevent violence among pregnant women in Kenya, training health care providers should go hand in hand with interventions sensitising and mobilising community members, both addressing the socio-demographic drivers of IPV during pregnancy and directing a particular attention to the most vulnerable ones.